Late relapse of progressive multifocal leucoencephalopathy postallogenic transplant in a young patient with CLL. (5th August 2013) - Sanchez-Quintana, Ana; Breña-Atienza, Joaquín; Marrero-Santos, Carmen; Alvarez-Acosta, Luis
Abstract : We describe a case of progressive multifocal leucoencephalopathy (PML) in a 39-year-old patient diagnosed with chronic lymphocytic leukaemia (CLL) who underwent two allogenic matched-sibling stem cell transplantations. PML was confirmed just after the first transplantation with cerebral MRI and by PCR in the cerebrospinal fluid. After immunosuppression withdrawal and cidofovir treatment, he achieved a reversal of clinical symptoms, John Cunningham (JC) virus positivity and MRI lesions regression. He remained asymptomatic for 5 years with no signs of infection activity, even though he received three new chemotherapy regimens due to a CLL relapse. However, after the second stem cell transplantation, new neurological symptoms began and a reactivation of the JC virus infection was detected. This time, treatment with mefloquine was started, but he experienced a progressive neurological deterioration and died 1 month after the symptoms began.